(untitled) (Revista Brasileira de Contabilidade e Gestão, 2021)
In view of the depletion of natural resources and the pollution of the environment, discussion about current consumption patterns and the way in which institutions have been developing their activities was stimulated. One of the proposals is to think aboutthe reuse of products that have already been created, for this, manufacturing emerges as a process that brings environmental and economic advantages. Therefore, this article aims to investigate the proposed studies on remanufacturing and general systems theory, as we live with different systems in our daily lives, in the last ten years in the Web Of Science. For this, it adopted a bibliometric analysis. The analysis of publications in the Web of Science database resulted in 2212 articles and it was found that the number of studies on the subject in the period between 2011 and 2020 has been increasing gradually. As for the number of articles by country, the United States leads the ranking of publications, followed by China. Among the types of productions, the article format is the most chosen among researchers.